Relative Price Changes of Ecosystem Services: Evidence from Germany - Jonas Heckenhahn; Moritz A. Drupp (Center for Economic Studies and ifo Institute (CESifo), 2022)
Discounting future costs and benefits is a crucial yet contentious practice in the appraisal of long-term public projects with environmental consequences. The standard approach typically neglects that ecosystem services are not easily substitutable with manufactured goods and often exhibit considerably lower growth rates. Theory has shown that we should either apply differentiated discount rates, such as a lower environmental discount rate, or account for increases in relative scarcity by uplifting environmental values. Some governments already integrate this into their guidance, but empirical evidence is scarce. We provide first comprehensive country-specific evidence, taking Germany as a case study. We estimate growth rates of 15 ecosystem services and the degree of limited substitutability based on a meta-analysis of 36 willingness to pay studies in Germany. We find that the relative price of ecosystem services has increased by more than four percent per year in recent decades. Heterogeneity analysis suggests that relative price changes are most substantial for regulating ecosystem services. Our findings underscore the importance of considering relative price adjustments in governmental project appraisal and environmental-economic accounting.
Keywords: D61; H43; Q51; Q54; Q58; 330; willingness to pay; discounting; relative prices; ecosystem services; substitutability; growth; cost-benefit analysis